H3K27M neoepitope vaccination in diffuse midline glioma induces B and T cell responses across diverse HLA loci of a recovered patient - Boschert, Tamara; Kromer, Kristina; Lerner, Taga; Lindner, Katharina; Haltenhof, Gordon; Tan, Chin Leng; Jähne, Kristine; Poschke, Isabel; Bunse, Lukas; Eisele, Philipp; Graßl, Niklas; Mildenberger, Iris; et al. (Science advances, 2024)
H3K27M, a driver mutation with T and B cell neoepitope characteristics, defines an aggressive subtype of diffuse glioma with poor survival. We functionally dissect the immune response of one patient treated with an H3K27M peptide vaccine who subsequently entered complete remission. The vaccine robustly expanded class II human leukocyte antigen (HLA)-restricted peripheral H3K27M-specific T cells. Using functional assays, we characterized 34 clonally unique H3K27M-reactive T cell receptors and identified critical, conserved motifs in their complementarity-determining region 3 regions. Using detailed HLA mapping, we further demonstrate that diverse HLA-DQ and HLA-DR alleles present immunogenic H3K27M epitopes. Furthermore, we identified and profiled H3K27M-reactive B cell receptors from activated B cells in the cerebrospinal fluid. Our results uncover the breadth of the adaptive immune response against a shared clonal neoantigen across multiple HLA allelotypes and support the use of class II-restricted peptide vaccines to stimulate tumor-specific T and B cells harboring receptors with therapeutic potential.
Online veröffentlicht: 2. Februar 2024
Gesehen am 19.08.2024